Kepatuhan Minum Obat ARV terhadap Kualitas Hidup Odha - Cecilia Angelica Harianja; Novita Hasiani Simajuntak; Calvien Douglas M Sembiring; Charly Glorya P Situmorang; Mutiara Sari Pasaribu (Institut Nalanda, 2026)
Human Immunodeficiency Virus (HIV) weakens the immune system and can lead to Acquired Immunodeficiency Syndrome (AIDS), making the body vulnerable to infections and certain cancers. Globally, around 35 million people live with HIV, and about 19 million are unaware of their status. In Indonesia, 48,300 new HIV cases and 9,280 AIDS cases were reported in 2017, with 62% occurring in males. Combination antiretroviral therapy (ART) is the most effective treatment for people living with HIV/AIDS (PLWHA) and has significantly reduced mortality while improving patients’ quality of life. However, treatment success strongly depends on medication adherence. This study aimed to determine the relationship between ART adherence and the quality of life of PLWHA in the working area of UPT Puskesmas Helvetia, Medan. An observational analytic study with a cross-sectional design was conducted from July to August 2025 using total sampling of patients receiving ART. Data were analyzed using the Chi-square test in SPSS version 27. The results showed that most respondents had good quality of life (39 respondents) and good ART adherence (39 respondents), with a significant relationship between ART adherence and quality of life (p < 0.001). These findings indicate that better adherence to ART is associated with improved quality of life among PLWHA.